The variability of multi-drug resistance ABCB1 gene in the Roma population from Croatia - Zajc Petranović, Matea; Tomas, Željka, biologinja; Škarić-Jurić, Tatjana; Smolej-Narančić, Nina; Janićijević, Branka; Stojanović Marković, Anita; Peričić Salihović, Marijana (2019)
When overexpressed, a large transmembrane P-glycoprotein, the product of the ABCB1 gene, is a notable impediment to brain-targeted therapies (like antiepileptics) and chemotherapies. Some of the genetic biomarkers with evidence of multi-drug resistance in ABCB1 ― rs1045642, rs1128503, and rs3213619 ― were analyzed in 440 subjects, members of three socio-culturally different Roma (Gypsy) groups of Croatia. Minor allele frequencies (MAFs) of rs1045642 and rs1128503 were the highest in the Balkan Roma (63.6% and 69.4%, respectively) when compared to the Baranja (52.3% and 62.5%) and the Međimurje Roma (48.8% and 54.5%) (p=0.0005 and p=0.0011, respectively). rs3213619 was monomorphic in the Međimurje group, while its MAFs in other two Roma groups were very low (<1.9%). The distribution of five detected haplotypes (four in the Međimurje group) significantly differed between the Roma subpopulations (p<0.0001), just like the frequencies of diplotypes (p=0.0008). At a global scale, the positive relationship between genetic and geographic distances between the 21 investigated populations indicates isolation by spatial distance. However, this is not true for the relationship between Roma and other populations due to their population history. The analyzed ABCB1 loci indicate genetic distinctiveness of the Roma population.
Bibliografija: 44 jed.
Abstract.
Keywords: Geni -- Romi -- Farmakogenetika -- Farmakorezistentnost; Hrvatska